2022
DOI: 10.3390/foods11223628
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Investigation of Macro-Composition and Volatile Compounds in Spring-Picked and Autumn-Picked White Tea

Abstract: The flavour of white tea can be influenced by the season in which the fresh leaves are picked. In this study, the sensory evaluation results indicated that spring-picked white tea (SPWT) was stronger than autumn-picked white tea (APWT) in terms of the taste of umami, smoothness, astringency, and thickness as well as the aromas of flower and fresh. To explore key factors of sensory differences, a combination of biochemical composition determination, widely targeted volatilomics (WTV) analysis, multivariate stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 85 publications
2
18
0
Order By: Relevance
“…Therefore, the thickness had a positive correlation with almost all critical metabolites. The thickness had a positive correlation with most of the tea polyphenols, which was also found as a contributor to the thickness of white tea . The thickness was also positively correlated with most of the organic acids except shikimic acid, which is in agreement with the result of Fan et al The numb sensation showed a significantly positive correlation with 4- p -COQA and quercetin-3- O -β- d -glucoside.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Therefore, the thickness had a positive correlation with almost all critical metabolites. The thickness had a positive correlation with most of the tea polyphenols, which was also found as a contributor to the thickness of white tea . The thickness was also positively correlated with most of the organic acids except shikimic acid, which is in agreement with the result of Fan et al The numb sensation showed a significantly positive correlation with 4- p -COQA and quercetin-3- O -β- d -glucoside.…”
Section: Resultssupporting
confidence: 89%
“…The thickness had a positive correlation with most of the tea polyphenols, which was also found as a contributor to the thickness of white tea. 26 The thickness was also positively correlated with most of the organic acids except shikimic acid, which is in agreement with the result of Fan et al 40 The numb sensation showed a significantly positive correlation with 4-p-COQA and quercetin-3-O-β-D-glucoside. The astringent mouthfeel was positively correlated with catechins, kaempferol, quercetin, and myricetin derivatives and organic acids.…”
Section: ■ Materials and Methodssupporting
confidence: 89%
See 2 more Smart Citations
“…The technology we use was widely-targeted volatile method, and the method of reference ( 21 ) was followed with minor changes. DB-5MS capillary column (30 m × 0.25 mm × 0.25 μm, Agilent J&W Scientific, Folsom, CA, United States), the flow rate of GC carrier gas (helium) was 1.2 mL/min, the temperature of the injection port was 250°C, no shunt injection, and the solvent is delayed for 3.5 min.…”
Section: Methodsmentioning
confidence: 99%